Konstitusionalitas Tata Kelola Pungutan Otoritas Jasa Keuangan (OJK) Dalam Keuangan Negara - Icha Cahyaning Fitri; Yusuf Adiwibowo; Eka N.A.M. Sihombing (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2026)
This study aims to analyze the mechanisms of fees collected by Indonesia’s financial sector regulator in comparison with other countries, as well as the legality of these fees and the reporting of the OJK’s budget utilization. This study is a normative legal study employing a statutory approach, a conceptual approach, and a comparative approach to the models of financial sector regulatory agencies in Japan and Germany. The results of the study indicate that OJK levies possess the characteristics of public revenue because they derive from state authority, are compulsory in nature, and are used to finance the oversight functions of the financial services sector. However, the regulations governing the use of these levies in Government Regulations have not been fully integrated into the state treasury mechanism, thereby creating a normative inconsistency with the principles of state financial management under Article 23A of the 1945 Constitution of the Republic of Indonesia. This study concludes that the constitutionality of OJK levies requires clarification of their status as part of the state treasury. Therefore, a revision of Government Regulation No. 41 of 2024 is necessary, particularly regarding restrictions on the use of surplus levies across fiscal years, the obligation to deposit surplus levies into the state treasury, and the harmonization of the OJK’s financial reporting system with Government Regulation No. 71 of 2010 on Government Accounting Standards through the separation of reporting for state budget funds and levy funds. Furthermore, all uses of levy funds must be comprehensively audited by the State Audit Agency (BPK) and supervised by the House of Representatives (DPR) to ensure transparency, fiscal accountability, and legal certainty in the management of state finances.